A Lesson Learned From the Crisis Period: Will Borrowers Be Penalized After a Drawdown? - Hsiao, Daniel; Hu, Yan (Journal of Applied Business and Economics, 2022)
Large firms draw down lines of credit and add to existing credit facilities in response to the crisis of global pandemic. We examine whether borrowers are penalized with higher rates and stringent contract terms on new bank loans after drawdowns of credit lines. Our results show that borrowers are punished by various contract dimensions after a drawdown. The post-drawdown punishment is tempered to the borrowers of banks with high reputation. Last, we learn the lesson that the post-drawdown punishment is strengthened during the global financial crisis period, and our findings offer managerial implications referring to the impacts of similar crisis.